Penetapan Kadar Saponin dalam Gambas (Luffa acutangula L.) Hasil Pengeringan Matahari dan Pengeringan Oven Menggunakan Metode Gravimetri - Fitrianingsih, Natasya Hanindita; Lindawati, Novena Yety (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2023)
Gambas fruit or oyong or often called ceme (Luffa acutangula L) or ridged gourd is a plant that belongs to the Cucurbitaceae family. Gambas fruit contains several important nutrients and also contains several chemical compounds, one of which is saponin which can be useful as an experctorant, antitussive, antidiabetic, anticholesterol, anticancer, antibacterial and antifungal. This research was conducted with the aim of knowing the differences in saponin levels and differences in yield in sun-dried and oven-dried squash fruits. Differences in temperature and drying method may allow for differences in the yield and saponin levels in the squash. Determination of saponin levels was carried out using the gravimetric method which was the advantage of not requiring a comparator (standard saponins). The result showed that the sun drying yield was 8,24% with ±SD 0,00021 and the oven drying yield was 7,21% with ±SD 0,02821 while the saponin content in sun drying was 0,39% with a coefficient of variation of 0,001% and oven drying saponin content of 11,96% with a coefficient of variation of 0,002%.